Dendritic Spine Alterations in Schizophrenia - Moyer, Caitlin E. (Neurosci Lett, 2014)
Schizophrenia is a chronic illness affecting approximately 0.5–1% of the world’s population. The etiology of schizophrenia is complex, including multiple genes and contributing environmental effects that adversely impact neurodevelopment. Nevertheless, a final common result, present in many subjects with schizophrenia, is impairment of pyramidal neuron dendritic morphology in multiple regions of the cerebral cortex. In this review we summarize the evidence of reduced dendritic spine density and other dendritic abnormalities in schizophrenia, evaluate current data that informs the neurodevelopment timing of these impairments, and discuss what is known about possible upstream sources of dendritic spine loss in this illness.